Belle Vie' Café (Café) / Athirah Abdul Aziz ... [et al.] - Athirah, Abdul Aziz; Iika Qistina, Mohd Azahari; Hairin Syafida, Hadiman; Nur Amirah Nazila, Mohd Nazri; Nur Syuhada, Jamalludin (2019)
This business is based on partnership where it consists of five members which hold an important position in this business which are general manager, financial manager, marketing manager, operational manager and administrator manager. This business capital amounted to RM where the total contribution of each member is RM and the balance is from Maybank's loan. Bellle Vie Cafe is one of the popular cakes cafe at Seri Iskandar where many people pay a visit during weekends to have our delicious cakes. Our shop is easy to reach as it is located near to the mall. Our cafe concept which is vintage is one of the reasons why many people come to pay a visit as they wanted to take picture at our cafe. Belle Vie Cafe is a cafe that focused in serving cakes. The cakes are using premium ingredients to improve the tastes of the cakes. The cakes that our cafe serves come from different shape and size to make it looks interesting and attractive to be serve at the customers. Moreover, we do improve the tastes of our cakes to make it more delicious by trying to add and to less the ingredient needed for each of the cakes. We are looking forward to make our cafe goes viral and to be well-known all around Malaysia. Every month we had a meeting between our partners in order to develop marketing strategy and ideas on how to improve our sales and attract more people to come to our shop. Currently one of our marketing strategy is give a discount to student since most of our customer are students from the nearest universities. Other than that, we make some innovation by implying our creativity and modem element in baking the cakes. We make a different look of our cakes by making a various colour of cake rather than the usual. The more attractive the cakes, the more people would give a try. Last but not least, we are planning to open more branch around the Malaysia and we want our cafe name become established in 7 to 9 years in the future. We also hoping that we will always fulfill the demand from our customers.